2022
DOI: 10.1111/jcpe.13696
|View full text |Cite
|
Sign up to set email alerts
|

Anterior implant restorations with a convex emergence profile increase the frequency of recession: 12‐month results of a randomized controlled clinical trial

Abstract: Aim: To test whether the emergence profile (CONVEX or CONCAVE) of implantsupported crowns influences the mucosal margin stability up to 12 months after insertion of the final restoration.Materials and Methods: Forty-seven patients with a single implant in the anterior region were randomly allocated to one of three groups: (1) CONVEX (n = 15), implant provisional and an implant-supported crown both with a convex profile;(2) CONCAVE (n = 16), implant provisional and an implant-supported crown both with a concave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…In the present study, only maxillary premolars were included, and mucosa measurements were initiated at different time points (implant placement vs. crown placement). Thus, differences in the inclusion criteria and evaluation time points may in part explain differences in the observed outcomes with the previously mentioned study (Siegenthaler et al, 2022).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In the present study, only maxillary premolars were included, and mucosa measurements were initiated at different time points (implant placement vs. crown placement). Thus, differences in the inclusion criteria and evaluation time points may in part explain differences in the observed outcomes with the previously mentioned study (Siegenthaler et al, 2022).…”
Section: Discussionmentioning
confidence: 69%
“…placement). Thus, differences in the inclusion criteria and evaluation time points may in part explain differences in the observed outcomes with the previously mentioned study (Siegenthaler et al, 2022).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…At the same time, cross-sectional studies (Katafuchi et al, 2018;Majzoub et al, 2021;Yi et al, 2020) have suggested that overcontouring of the prosthesis more than 30°as it appears in peri-apical radiographs is correlated with an increased risk for peri-implantitis in bone-level implants. Finally, the convexity of the prosthesis profile has been correlated with increased recession (Siegenthaler et al, 2022), marginal bone loss (Valente et al, 2020), and when combined with overcontouring, peri-implantitis (Yi et al, 2020).…”
Section: Overcontouring Of the Prosthesis Emergence Angle And Clinica...mentioning
confidence: 99%